How to teach empathy to future nurses? an integrative literature review (Research, Society and Development, 2020)
Objective: The present study aims to search for the scientific production available on teaching methods of empathy for nursing students. Method: qualitative integrative review carried out on the CAPES Journal Portal, using as criteria for the selection of available journals: indexing to EMBASE and indexing to MEDLINE. Results: The analysis of the data contained in the articles was carried out according to Bardin's content analysis technique. Different methods of teaching and improving empathy were reported, as well as different ways of measuring their learning. Techniques that bring proximity to the patient's reality were in evidence in most studies. Conclusion: The importance of training nurses with empathic domains and their relationship with humanized care and effective treatment was perceived. The teaching of emotions is becoming more evident, but there is still a need to increase the debate and expand scientific production on the subject.